Mesh-free Particle Method for Simulation of Earthquake-induced Slope Failure - Ono, Yusuke (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The Smoothed Particle Hydrodynamics (SPH) method for simulation of earthquake induced slope failure is presented. The SPH method was first invented for simulating dynamic behavior of compressive viscous fluid in the late 1970s and has been applied to other various problems in engineering field. So far the SPH method has been extended to handle not only fluid dynamics but also solid dynamics. The most advantage of the SPH method compared to other well established numerical method, such as the Finite Element Method, the Finite Discrete Method et al., is feasibility of analyzing discontinuity problem. This feature of the SPH method is desirable to earthquake induced slope failure simulation because slope failure phenomena posses discontinuity inherently. In this paper, the SPH method is adapted to simulate the earthquake induced slope failure. The SPH method can describe full dynamic behavior of a slope excited by earthquake and possible to predict the final configuration of slope after failure.